2018
DOI: 10.1097/ogx.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pelvic Pain in an Interdisciplinary Setting: 1-Year Prospective Cohort

Abstract: (Abstracted from Am J Obstet Gynecol 2018;218:114.e1–114.e12) Chronic pelvic pain (CPP) is a common clinical problem among women. Its etiology is complex and involves an interplay of gynecologic, urologic, gastrointestinal, musculoskeletal, and psychosocial comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…showed a decrease in those with PPP needing ED visits from 24% to 11% ( P < 0.001) 12 months post their interdisciplinary clinic attendance. This study also found a reduction in general physician visits from 73% to 36% ( P < 0.001) and improvement in self‐reported pain scores, although these are outcomes that were not measured through our study 9 …”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…showed a decrease in those with PPP needing ED visits from 24% to 11% ( P < 0.001) 12 months post their interdisciplinary clinic attendance. This study also found a reduction in general physician visits from 73% to 36% ( P < 0.001) and improvement in self‐reported pain scores, although these are outcomes that were not measured through our study 9 …”
Section: Discussionmentioning
confidence: 46%
“…Patients are discharged to their general practitioners after six months. A multidisciplinary approach to PPP has been shown to improve self‐reported pain and reduce emergency department (ED) presentations in other centres 8–10 …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, exercise has been successfully incorporated into multidisciplinary treatment programmes to treat female CPP [4,27]. Available evidence suggests that physical activity/ exercise as an intervention is associated with few adverse events and may improve pain intensity, physical function and consequently quality of life [28].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the MDTs in the management of CPP has been evaluated and confirmed by the very few available reports (22)(23)(24)(25)(26). Gupta et al (22) reported the experience of the Beaumont Health System, with the creation of a Multi-disciplinary Women's Urology Center, including not only urologists but also gynecologists, experts in pelvic floor physical therapies, colorectal surgeons, integrative medicine practitioners who provide alternative therapies such as acupuncture, and pain psychologists.…”
Section: Discussionmentioning
confidence: 89%